Assessing the Accuracy of Approximated Ephemeris Data for Prayer Time Calculations - Emye Tegar Handhita; Marwa Marwa; Fatum Abubakar; Ziaulrahman Mushkalamzai; Muhammad Fadhly (Al-Hilal: Journal of Islamic Astronomy, 2026)
Prayer (ṣalāh) is an obligatory act of worship in Islam, with its timing determined by astronomical parameters derived from ephemeris data. Although many mobile applications are available to calculate prayer times, most depend on internet connectivity, limiting their usability in certain conditions. As an alternative, prayer times can be determined independently using the hisab method, which requires ephemeris data. This study proposes using approximated ephemeris data and evaluates its accuracy in prayer-time calculations. A quantitative computational approach was employed by developing a Microsoft Excel-based model to generate approximated ephemeris data and calculate prayer times. The approximated data were compared with official ephemeris data from the Ministry of Religious Affairs of Indonesia over one year (2026) across multiple locations. The results indicate that the approximated ephemeris data produce only minor deviations, resulting in prayer time differences of a few seconds. These findings demonstrate that the approximation method can be reliably used, and the developed Excel-based tool provides a practical solution for offline prayer time determination.